Synthesis and Characterization of Starch Aerogel - Siaw Chien, Lee (Universiti Malaysia Sarawak (UNIMAS), 2015)
Aerogel is a material that has wide variety of applications throughout the world. It has the properties of large surface area, low density, high refractive index, low thermal conductivity, and low velocity of sound. Aerogel made from native sago starch are biodegradable and biocompatible which it can be used for the medical science applications. However, researches that had been done on the starch aerogels are still lacking. In this study, starch aerogels of different morphology were synthesized by varying the time, temperature, solvent exchange method, solvent exchange ratio, drying method and native sago starch to water ratio. The swelling studies and characterization of starch aerogel by using SEM were also studied. The increase in the duration of processing time and temperature helped in improving the pore structure of the starch aerogels. Besides, the increase in native sago starch to water ratio caused the decrease in the pore size of starch aerogel. In addition, the swelling behavior of the starch aerogels depends on both of the pore size and the gel network of starch aerogel.